Trust dan Kultur Organisasi Sebagai Penggerak Intellectual Capital terhadap Kinerja Organisasi - Partiwi Dwi Astuti (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2011)
AbstractThe purpose of study was the influence of trust and organizational culture to intellectual capital and its impact to organizational performance. Data was collected from 109 (21,80%) questionnaires were sent to financial managers in bank and financial institution companies at Bali, and analysis conducted by SEM. The results shows that trust and organizational cultures have an effect negatively and positively to intellectual capital elements. Human capital has an effect positively to customer capital and of structural capital. Customer capital has an effect positively to structural capital. Structural capital has an effect positively to organizational performance.Keywords: intellectual capital, trust, organizational culture, organizational performanceAbstrakTujuan penelitian ini adalah untuk menguji pengaruh trust dan budaya organisasi terhadap intellectual capital dan dampaknya terhadap kinerja organisasi. Data dikumpulkan dari 109 (21,80%) kuesioner yang dikirimkan kepada manajer keuangan bank dan lembaga keuangan di Bali, dan analisis menggunakan SEM. Hasil penelitian menunjukan bahwa trust dan budaya organisasi memiliki pengaruh negatif dan positif terhadap elemen intellectual capital. Human capital berpengaruh positif terhadap customer capital dan structural capital. Customer capital berpengaruh positif terhadap structural capital. Structural capital berpengaruh positif terhadap kinerja organisasi.Kata Kunci: intellectual capital, trust, budaya organisasi, kinerja organisasi